Designing Marketing Communication Strategy in the New Normal Era at Cafe Apung Rowo Klampok in Senggreng Village Sumberpucung District Malang Regency - Pratiwi, Fitri Retnowati; Kriyantono, Rachmat; Prasetyo, Bambang Dwi (Advances in Social Sciences Research Journal, 2023)
Cafe Apung Rowo Klampok is a floating-themed cafe located in the village of Senggreng, Sumberpucung District, Malang Regency. The establishment of cafes, coffee shops, and similar ventures has become one of the developments in the creative economy by capitalizing on existing opportunities. Meanwhile, the shift in lifestyle within society has transformed cafes into places of entertainment and an integral part of daily life, attracting entrepreneurs to explore cafe businesses. Consequently, numerous cafes have emerged in various regions, including in Senggreng. During the Covid-19 pandemic, Cafe Apung Rowo Klampok did not possess a marketing communication strategy to compete with its competitors. Marketing communication strategy is a crucial aspect for the successful operation of any business. This study aims to design a marketing communication strategy suitable for Cafe Apung Rowo Klampok in the New Normal Era using the SWOT analysis. This descriptive qualitative study adopted a constructivist paradigm and the SWOT analysis. The café’s factors were rated using the IFAS and EFAS matrices. The weighted scores were then used to ascertain the cafe’s position, which, in this case, places the café in Quadrant I, implying the need to apply an aggressive growth policy. The café is recommended to focus on utilizing its strengths and capitalizing on available opportunities as marketing strategies. The alternative strategies applicable to this cafe in the New Normal Era involve developing and enhancing both offline and online promotional efforts across various social media platforms, and leveraging technological advancements for marketing purposes, such as providing online delivery services.